Regenerated fibre Bragg grating fabricated on high germanium concentration photosensitive fibre for sensing at high temperature - Chong, Su Sin; Chong, Wu Yi; Harun, Sulaiman Wadi; Ahmad, Harith (Elsevier, 2012)
A Regenerated Fibre Bragg Grating (RFBG), with repeatable high temperature response between 400 °C1200 °C, has been demonstrated using a hydrogen-loaded, highly germanium-doped, photosensitive fibre. A wavelength shifts of as much as 20 nm is attained during temperature calibration up to 1300 °C. A large temperature response of 17 pm/°C is obtained from the RFBG, with very good repeatability.